The Correlation Between Environmental Sanitation and Stunting Case in Tamanrahayu Village, Setu District Area, Bekasi Regency in 2024 - Syahadah, Asma Amania; Nitami, Maymi; Mustikawati, Intan Silviana; Heryana, Ade (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background: The prevalence of stunting in Bekasi Regency in 2021 is 21.50% and in 2022 it is 17.8%. The highest stunting rate in the UPTD Puskesmas Setu II working area is in Tamanrahayu Village with a prevalence in 2022 of 8.17% and in 2023 of 6.12%. The environmental conditions of Tamanrahayu Village are directly adjacent to the Burangkeng Final Disposal Site (TPA) which serves the Bekasi Regency area. A preliminary study was conducted in Tamanrahayu Village with 10 cases of families with stunted toddlers. Based on the results of observations and observations of environmental sanitation, it was found that 70% was unhealthy. The aim of this research is to determine the relationship between hygiene and environmental sanitation on the incidence of stunting in Tamanrahayu Village, Setu District, Bekasi Regency in 2024. Method: Case control study design method. The population of this research is all mothers who have toddlers in Tamanrahayu Village and the sample is 80 respondents with 40 respondents as the case group and 40 respondents as the control group in TamanrPahayu Village, Setu District, Bekasi Regency using systematic random sampling. Results and Discussion: There are more toddlers with unhealthy environmental sanitation in the stunting group (75%) than those without stunting (17.5%). The results of statistical analysis using the Chi Square Test obtained a P value = <0.001, indicating that there is a significant relationship between environmental sanitation and the incidence of stunting in toddlers. Conclusion: Based on the results of the bivariate test, it can be concluded that there is a significant relationship between environmental sanitation and the incidence of stunting in toddlers. Suggestion: For the government to implement IYCF education on regular clean water checks, as well as sensitive interventions by providing access to sanitation for the community.